2020
DOI: 10.1093/icvts/ivaa271
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of robotically-assisted surgery for complex mitral valve repair

Abstract: OBJECTIVES To determine whether robotic mitral valve repair can be applied to more complex lesions compared with minimally invasive direct mitral valve repair through a right thoracotomy. METHODS We enrolled 335 patients over a 9-year period; 95% of the robotic surgeries were performed after experience performing direct mitral valve repair. RESULTS The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…Robotic surgery has been a major focus for cardiac surgeons. Robotic MVRep has been widely implemented in Europe and the United States as well as in Asian countries [ 12 – 17 ]. This study reported the clinical data and follow-up results of 120 Chinese patients receiving robotic mitral valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Robotic surgery has been a major focus for cardiac surgeons. Robotic MVRep has been widely implemented in Europe and the United States as well as in Asian countries [ 12 – 17 ]. This study reported the clinical data and follow-up results of 120 Chinese patients receiving robotic mitral valve surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also analyzed their entire robotic mitral experience over the same period in which 24% (of 500) was considered most complex (bileaflet repair or atrioventricular groove reconstruction for mitral annular calcification) and concluded that despite longer crossclamp time and cardiopulmonary bypass time, the patient outcomes have not worsened despite having more complex repairs. 11 Similarly, Fujita and colleagues 12 presented 9-year data on 335 patients undergoing either robotic or a minithoracotomy approach; 17% and 4% of the repairs, respectively, were considered most complex and the robotic approach was associated with excellent early outcomes.…”
Section: Robotic Approach For Complex Mitral Pathologymentioning
confidence: 99%
“…29,30 Some centers have assessed the feasibility of robotic-assisted MIMVS in a wide range of mitral pathologies with more complex repair techniques (e.g., bileaflet repair, mitral annular calcification excision). [31][32][33] Fujita et al reported that patients who underwent robotic-assisted MIMVS had a higher complexity score requiring more complex repairs than patients undergoing minithoracotomy MIMVS. 32 Neo-chord implantation was attempted more in robotic-assisted MIMVS though procedure times did not differ between the two groups.…”
mentioning
confidence: 99%
“…[31][32][33] Fujita et al reported that patients who underwent robotic-assisted MIMVS had a higher complexity score requiring more complex repairs than patients undergoing minithoracotomy MIMVS. 32 Neo-chord implantation was attempted more in robotic-assisted MIMVS though procedure times did not differ between the two groups. Regarding complexity, Rowe et al…”
mentioning
confidence: 99%